Enquiry into the Topology of Plasma Membrane-Localized PIN Auxin Transport Components - Nodzyński, Tomasz; Vanneste, Steffen; Zwiewka, Marta; Pernisová, Markéta; Hejátko, Jan; Friml, Jiří (Molecular plant, 2016)
Auxin directs plant ontogenesis via differential accumulation within tissues depending largely on the activity of PIN proteins that mediate auxin efflux from cells and its directional cell-to-cell transport. Regardless of the developmental importance of PINs, the structure of these transporters is poorly characterized. Here, we present experimental data concerning protein topology of plasma membrane-localized PINs. Utilizing approaches based on pH-dependent quenching of fluorescent reporters combined with immunolocalization techniques, we mapped the membrane topology of PINs and further cross-validated our results using available topology modeling software. We delineated the topology of PIN1 with two transmembrane (TM) bundles of five α-helices linked by a large intracellular loop and a C-terminus positioned outside the cytoplasm. Using constraints derived from our experimental data, we also provide an updated position of helical regions generating a verisimilitude model of PIN1. Since the canonical long PINs show a high degree of conservation in TM domains and auxin transport capacity has been demonstrated for Arabidopsis representatives of this group, this empirically enhanced topological model of PIN1 will be an important starting point for further studies on PIN structure-function relationships. In addition, we have established protocols that can be used to probe the topology of other plasma membrane proteins in plants.
Keywords: proteiny huseníčku; Hydrophobic and Hydrophilic Interactions; plasma membrane protein; Arabidopsis thaliana; Arabidopsis; hydrofobní a hydrofilní interakce; membránové transportní proteiny; Arabidopsis Proteins; kyseliny indoloctové; Membrane Transport Proteins; auxin efflux carriers; proteinové domény; Cell Membrane; cytoplazma; extracelulární prostor; Cytoplasm; Indoleacetic Acids; Extracellular Space; topology; buněčná membrána; Protein Transport; Protein Domains; transport proteinů